2012
DOI: 10.1016/j.neuroimage.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness changes following spatial navigation training in adulthood and aging

Abstract: A widespread network involving cortical and subcortical brain structures forms the neural substrate of human spatial navigation. Most studies investigating plasticity of this network have focused on the hippocampus. Here, we investigate age differences in cortical thickness changes evoked by four months of spatial navigation training in 91 men aged 20-30 or 60-70 years. Cortical thickness was automatically measured before, immediately after, and four months after termination of training. Younger as well as old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 87 publications
(105 reference statements)
3
74
0
Order By: Relevance
“…At least one study (Ceccarelli et al, 2009) also seems to have collected data for experimental and control groups at different time points. In addition, several studies performed group by time analyses only as secondary analyses (applying more liberal significance thresholds) after regions-of-interests (ROIs) had been identified in whole-brain analyses for time effects in the experimental group (such studies include Bezzola et al, 2011;Hölzel et al, 2011;Ilg et al, 2008;Scholz et al, 2009;Taubert et al, 2010;Wenger et al, 2012). Such a non-independent selection procedure biases results toward finding a group by time effect and should be avoided (see Kriegeskorte et al, 2009, for a review of this issue).…”
Section: Experience-dependent Changes In Regional Grey Matter Volume mentioning
confidence: 99%
See 1 more Smart Citation
“…At least one study (Ceccarelli et al, 2009) also seems to have collected data for experimental and control groups at different time points. In addition, several studies performed group by time analyses only as secondary analyses (applying more liberal significance thresholds) after regions-of-interests (ROIs) had been identified in whole-brain analyses for time effects in the experimental group (such studies include Bezzola et al, 2011;Hölzel et al, 2011;Ilg et al, 2008;Scholz et al, 2009;Taubert et al, 2010;Wenger et al, 2012). Such a non-independent selection procedure biases results toward finding a group by time effect and should be avoided (see Kriegeskorte et al, 2009, for a review of this issue).…”
Section: Experience-dependent Changes In Regional Grey Matter Volume mentioning
confidence: 99%
“…Also when the images are modulated, that is, when the required normalization is encoded into the voxels, so that each voxel represents a mix of volume and grey matter probability (the Jacobian voxel compression map multiplied by grey matter probability), the interpretation in terms of the biological brain is unclear. Other techniques to assess changes on T1-weighted MR images, such as manual segmentation , automatic techniques to measure regional brain volume (with e.g., tools such as FreeSurfer or FSL-FIRST; Erickson et al, 2011;Mårtensson et al, 2012), and automatic outlining of cortical thickness (with e.g., tools such as CIVIC and FreeSurfer; Engvig et al, 2010;Haier et al, 2009;Langer et al, 2012;Mårtensson et al, 2012;Wenger et al, 2012) are superior in this regard. For example, cortical thickness measures map onto known thickness of the brain in a valid manner (Fischl and Dale, 2000).…”
Section: Experience-dependent Changes In Regional Grey Matter Volume mentioning
confidence: 99%
“…Therefore, the BASE-II population consists of three subgroups (in the following called laboratory samples L1, L2 and L3) which differ with regard to their study provenience. L1 participants came from the formerly conducted COGITO study (Schmiedek et al 2010), while L2 participants are mainly from the Dopamine study (Li et al 2009) but also from the SPACE study Wenger et al 2012). Although recruited by the MPIB, most L3 participants had not yet participated in any MPIB study.…”
Section: Target Population(s)mentioning
confidence: 99%
“…As the SPACE participants represent a minor subgroup of the BASE-II participants (N<100), only the criteria from the COGITO and the Dopamine study are reported here. For further information of the SPACE criteria see Loevdén et al (2012) and Wenger et al (2012).…”
Section: Target Population(s)mentioning
confidence: 99%
“…For example, structural changes in cortical thickness are smaller in older than in younger adults after spatial navigation training (Wenger et al, 2012). Moreover, functional neuroplasticity, as measured by MEG and MRI, is reduced in older, relative to young adults after training on a motor sequence (Mary et al, 2015) and a working memory task (Heinzel et al, 2014).…”
Section: Neuroplasticity In Older Human Adultsmentioning
confidence: 99%